Early Cochlear Implantation Allows Deaf Children to Control Voice Pitch and Loudness independently. Issue 1 (January 2022) - Yamazaki, Hiroshi; Suehiro, Atsushi; Ueda, Yuko; Kondo, Kanako; Ishida, Ai; Yamamoto, Norio; Takagi, Akira; Omori, Koichi
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Congenitally deaf children with a cochlear implant (CI) improve their speech production intelligibility, but their prosody, including stress and intonation produced by voice pitch and loudness changes, often differs from normal hearing people, which affects their fluent oral communication. This study is aimed to clarify abnormal characteristics of voice pitch and loudness control in CI recipients using a newly developed visually guided pitch change task. Methods: We included 13 normal hearing volunteers (NH group) and 17 congenitally deaf CI users who showed good speech intelligibility. The 17 CI users were divided into Early-CI and Late-CI groups, based on their age at implantation of 2.5 years. Using the visually guided pitch change task and acoustic voice analysis of sustained vowels, we assessed their vocal skills to maintain constant pitch and loudness and intentionally change the voice pitch independent from loudness. At the time of examination, the mean age was 24.1, 12.7, and 18.9 years in the NH, Early-CI, and Late-CI groups. Results: During constant vowel production, Early-CI and Late-CI groups showed more significant fluctuations in pitch and loudness than the NH group. However, when focusing on intentionally changing only the pitch of the voice, the Early-CI group was significantly better than the Late-CI group and comparable to the NH group in terms of their ability to change vocal pitch independently from loudness. Conclusion: Among congenitally deaf patients, age at implantation was associated with the development of voice skills to control voice pitch and loudness separately, which may influence their fluent prosody production.